The Differences in the Result of Examination of Adolescent Hemoglobin Levels Using Sahli And Digital Methods (Easy Touch GCHb) - Estri Kusumawati; Nova Lusiana; Ika Mustika; Sri Hidayati; Esti Novi Andyarini (State Islamic University of Sunan Ampel, 2018)
The incidence of anemia is the ten most significant health problems today. The prevalence of anemia in an adolescent is still quite high, ranging from 40-88%. Anemia is a medical condition with a red blood cell count or hemoglobin level <12 gram/100ml. Hemoglobin levels can be determined in various ways, including visual methods and digital methods usingGCHb easy touch. The purpose of this study was to identify differences in the results of adolescent hemoglobin (Hb) examination using Hb Sahli and Easy Touch GCHb at Sunan Ampel State Islamic University Surabaya. The research method used is descriptive comparative, with purposive sampling technique. The results of Hb level examination with Hb Sahli method, it is known that 86,7% (52 respondents) experienced anemia while the results of the test using the easy touch GCHb method by 15% (9 respondents) experienced anemia. There are differences in the results of Hb level examination with the Sahli method and the Easy Touch GCHb with a significance value of 0,000.